Dextran Producing Bacteria: A Literatur Review - Salsabilla, Vishtari; Putri, Dwi Hilda; Advinda, Linda; Achyar, Afifatul; Wibisana, Ahmad (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
This study aims to analyze dextran-producing bacteria, especially from the general Leuconostoc, Weissella, and Lactobacillus, which produce the enzyme dextransucrase for dextran synthesis. This research uses the Systematic Literature Review (SLR) method based on the PRISMA protocol, with data sources from various trusted scientific databases for the 2020–2024 period. The results of the study show that variations in dextran structure, such as molecular weight and degree of branching, are highly dependent on the bacterial strain and fermentation conditions. Optimization of production parameters, including pH, temperature and substrate concentration, can increase dextran production efficiency The conclusions of this study emphasize the need for a multidisciplinary approach to optimize the potential of dextran in industrial and biotechnology applications. Further research is recommended to explore new strains, optimize production processes, and diversify dextran applications.